Flavor Fatigue: Cognitive Depletion Influences Consumer Enjoyment of Complex Flavors - Hildebrand, Diogo; Rubin, Dan; Hadi, Rhonda; Kramer, Thomas (Journal of Consumer Psychology, 2021)
Surprisingly, little research has examined how consumer responses to specific flavor characteristics of food are formed or how they may fluctuate situationally. We address this lacuna in the literature on the hedonic appreciation of food by demonstrating that enjoyment along one important gustatory dimension, flavor complexity, varies with the degree to which consumers are mentally depleted. Specifically, showing that gustatory sensations are more cognitively demanding than previously thought, findings from three studies evince that cognitive depletion reduces consumer enjoyment of complex‐flavored (but not simple‐flavored) foods via a reduction in pleasure that otherwise can be derived from complex flavors. We establish this effect across three different food categories and provide preliminary evidence for consumers’ ability to identify flavors as the underlying process. Our findings offer theoretical contributions and avenues for future research.